Frequency and cost of acute surgical admissions in over‐anticoagulated patients: over‐anticoagulation in the community. Issue 4 (1st December 2016) - Nimmo, Moea; Armstrong, Delwyn; Koea, Jonathan B.
Abstract : Background: Anticoagulation treatment in the community is common. This investigation was undertaken to determine the frequency of patient surgical admission with conditions associated with over‐anticoagulation in the community and the surgical resource required to effectively and safely manage these patients acutely. Methods: Hospital discharge data on individual patients admitted to Waitemata District Health Board hospitals between December 2014 and November 2015 inclusive were reviewed. Data were extracted on individual patients with relevant ICD‐10 codes (D683, Y442, Y443). Individual records for patients admitted to general surgery were then reviewed and costing information related to admissions extracted. Results: A total of 551 patients were admitted in a 12‐month period (4.8 admissions/1000 warfarin users and 2.4 admissions/1000 dabigatran users) for conditions associated with over‐anticoagulation, with 35 admitted to the general surgery service, of whom 29 were taking warfarin and six taking dabigatran. A total of 21 patients were admitted with haemorrhagic conditions, and 14 over‐anticoagulated patients were admitted with general surgical conditions requiring treatment. All patients were managed by withholding anticoagulant medication, 12 required formal reversal, three required red cell transfusion and four haemostatic procedures. The average hospital stay was 4 days, with inpatient costs of NZ3500. Conclusion: Management of patients admitted with over‐anticoagulation in the community is a significant surgical workload; however, acute management is usually straightforward.